AN ANALYSIS OF CONNOTATIVE MEANING IN LINKIN PARK “A THOUSAND SUNS ALBUM” - Heldestina Laia; Sitasi Zagoto; Senadaman Wau (Universitas Nias Raya, 2022)
This research aimed to analyze the connotative meaning and the type of connotative meaning found in the twelve lyrics of linkin parks’s songs. This research is designed in qualitative research with descriptive approach. The source of this research is the twelve lyrics of linkin park’s songs. The data is analyzed by using the technique of the data analysis: data condensation, data display, drawing and verifying conclusions. The result of data analysis shows that: there are 30 connotative meaning used in the twelve lyrics and the dominant types of connotative meaning is associative meaning. Besides, it is found 16 associative meaning, 4 allusive meaning, 3 collocative meaning, 7 affective meaning, 0 reflective meaning and attitudional meaning. Based on the finding, it is concluded that the connotative meaning found is carried within words, phrase and sentences in twelve lyrics of linkin parks’s song. In this research, the researcher also wants to suggest the lecturer or the English teacher to lead the students’ use the connotative meaning theory as the material of teaching and learning and also can be implemented as material for increasing the students’ ability in mastering the vocabullary and also connotative meaning material can be propossed to extend students ability in recognizing the meaning of words not only which has provided in dictionary but also which has associated in another aspect.